2022
DOI: 10.3390/jcm11175063
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of COVID-19 Lockdown in Neovascular AMD Patients in Spain: Structural and Functional Outcomes after 1 Year of Standard Follow-Up and Treatment

Abstract: Consequences of the COVID-19 pandemic on medical care have been extensively analyzed. Specifically, in ophthalmology practice, patients suffering age-related macular degeneration (AMD) represent one of the most affected subgroups. After reporting the acute consequences of treatment suspension in neovascular AMD, we have now evaluated these same 242 patients (270 eyes) to assess if prior functional and anatomical situations can be restored after twelve months of regular follow-up and treatment. We compared data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The BCVA and anatomical findings of the patients did not return to the pre-pandemic status even after 1 post-pandemic year, which is consistent with the results of previous studies [16,17]. However, these results should be interpreted with caution because patients with nAMD may exhibit a worsening long-term course despite receiving appropriate treatment during the follow-up period [18,19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The BCVA and anatomical findings of the patients did not return to the pre-pandemic status even after 1 post-pandemic year, which is consistent with the results of previous studies [16,17]. However, these results should be interpreted with caution because patients with nAMD may exhibit a worsening long-term course despite receiving appropriate treatment during the follow-up period [18,19].…”
Section: Discussionsupporting
confidence: 87%
“…However, there is a gap in these previous studies as they did not consider the impact of natural disease progression on nAMD [18,19], given that they did not compare it with a control group receiving timely treatment. In fact, although BCVA did not recover in a previous study, anatomic deterioration was reported to be fully restored [16]. Moreover, no study has applied a follow-up period of more than 2 years.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation